Síntesis de bioplásticos a partir de microorganismos (2017)
The article analyzes the general panorama of the production of bioplastics, as well as the properties of the polyhydroxyalkanoates (PHA) and the conditions for their production: temperature, pH, time, agitation, sustrate, culture media and microorganism. The research proposes that the production of bioplastics derived from microorganisms is an alternative to the environmental problems generated by the use of plastics produced by the petrochemical industry. This study describes the synthesis of the biopolymer according to the types of bacteria: those that have the limitation of an essential nutrient for the production of secondary metabolites and those that do not require limitation of nutrients because they produce the biopolymer during the growth phase. The study concludes that it is necessary to evaluate other types of microorganisms to obtain a better yield and a higher production of bioplastic.